2004
DOI: 10.1007/s10265-004-0162-6
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of mitochondrial genes is caused by interactions between the nucleus of Brassica rapa and the cytoplasm of Diplotaxis muralis in the leaves of alloplasmic lines of B. rapa

Abstract: In Brassica species, alloplasmic lines displaying cytoplasmic male sterility (CMS) are established by combining the nucleus from B. rapa with the cytoplasm from Diplotaxis muralis. The failure to observe restriction fragment length polymorphism (RFLP) patterns of mitochondrial genes ( coxII, coxIII, atpA, atp6, atp9, cob, nad3, nad6, and nad9) between alloplasmic lines of B. rapa and D. muralis indicates that introgression of the B. rapa nucleus into the cytoplasm of D. muralis does not cause any alterations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…Increased levels of mitochondrial mRNAs have been reported for alloplasmic lines of Brassica rapa carrying the cytoplasm of Diplotaxis muralis (Yamasaki et al 2004). The authors postulate that this enhanced expression results from novel nucleo-mitochondrial interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of mitochondrial mRNAs have been reported for alloplasmic lines of Brassica rapa carrying the cytoplasm of Diplotaxis muralis (Yamasaki et al 2004). The authors postulate that this enhanced expression results from novel nucleo-mitochondrial interactions.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of the plant materials used in the present study have been reported elsewhere (Hinata and Konno, 1979;Yamasaki et al, 1998;Yamasaki et al, 2004). In brief, three euplasmic lines of B. rapa (maintainer lines), its wild relative D. muralis, and three alloplasmic lines of B. rapa were used in the present study (Table 1; Fig.…”
Section: Plant Materialsmentioning
confidence: 99%
“…In flower buds, additional production of a 2.5-kb coxI transcript and reduced accumulation of nad3 mRNA occur in three alloplasmic lines of B. rapa (MS-Yukina, MS-Kabu, and PMS-Hakusai) vs. D. muralis (Yamasaki et al, 1998). In the leaves, overexpression of atpA, atp6, atp9, cob, coxII, coxIII, and nad6 was detected in MS-Kabu and PMS-Hakusai vs. D. muralis (Yamasaki et al, 2004). However, the differences observed in the degree of male sterility among the three alloplasmic lines of B. rapa could not be attributed to differences in the expression of mitochondrial genes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In more than 300 higher plant species (Liu et al 2001), CMS is caused by the incompatibility between the nucleus and cytoplasm. Moreover, it is often induced by interspecies or inter-generic sexual crosses or asexual protoplast fusion (Yamasaki et al 2004;Liu et al 1996;Hirata et al 2001;Motegi et al 2003). Since CMS was discovered at the beginning of the twentieth century, they have been widely explored and applied for the production of hybrid crop seeds.…”
Section: Introductionmentioning
confidence: 99%